Drought enhances folivory by shifting foliar metabolomes in Quercus ilex trees. Issue 3 (21st January 2014) - Rivas‐Ubach, Albert; Gargallo‐Garriga, Albert; Sardans, Jordi; Oravec, Michal; Mateu‐Castell, Laia; Pérez‐Trujillo, Míriam; Parella, Teodor; Ogaya, Romà; Urban, Otmar; Peñuelas, Josep
Summary: At the molecular level, folivory activity on plants has mainly been related to the foliar concentrations of nitrogen (N) and/or particular metabolites. We studied the responses of different nutrients and the whole metabolome of Quercus ilex to seasonal changes and to moderate field experimental conditions of drought, and how this drought may affect folivory activity, using stoichiometric and metabolomic techniques. Foliar potassium (K) concentrations increased in summer and consequently led to higher foliar K : phosphorus (P) and lower carbon (C) : K and N : K ratios. Foliar N : P ratios were not lowest in spring as expected by the growth rate hypothesis. Trees exposed to moderate drought presented higher concentrations of total sugars and phenolics and these trees also experienced more severe folivory attack. The foliar increases in K, sugars and antioxidant concentrations in summer, the driest Mediterranean season, indicated enhanced osmoprotection under natural drought conditions. Trees under moderate drought also presented higher concentrations of sugars and phenolics; a plant response to avoid water loss. These shifts in metabolism produced an indirect relationship between increased drought and folivory activity.